Recycling aerated concrete waste as aggregate to produce eco‐friendly foamed mortar (EFM) - Sarıgül, Ertuğrul; Bayraktar, Oğuzhan Yavuz; Yüksel, Mustafa; Jamal, Ahmed Salah; Kara, Halil Oğuzhan; Ayyıldız, Mehmet Ali; Kaplan, Gökhan (Wiley, 2025)
AbstractNon‐structural components are difficult to recycle into fresh concrete due to their high porosity, high water absorption, and low strength. This study uses aerated concrete waste (ACW) as a case study to investigate the effect of recycled concrete aggregate on the performance of eco‐friendly foamed mortar (EFM). The results show that while incorporating ACW reduces fluidity and mechanical properties due to its porous structure, it enhances the lightweight and thermal insulation capabilities of EFM, making it suitable for non‐structural applications. When 25% ACW is applied, the 28‐day compressive strength (CS) of plain EFM decreases by 64.82%, while the hardened unit weight and thermal conductivity decrease by 17.49% and 30.85%, respectively. The addition of PPF compensates for the mechanical strength loss from ACW, with the bridging effect of PPF inhibiting crack formation and interlocking with aggregates and cement paste, though it further reduces fluidity. When 0.5% PPF is applied, the 7‐ and 28‐day flexural strength of the plain EFM increased by 77.35% and 30.54%, but this resulted in a 22.22% reduction in fluidity. This study presents a feasible approach for recycling low‐grade construction waste in EFM production, contributing to the development of sustainable construction materials.